Performance of multi-wavelength erbium doped fiber laser on free space optical medium - Boroon, Moahammad; Hitam, Salasiah; Mahdi, Mohd Adzir; Sahbudin, Ratna Kalos Zakiah; Seyedzadeh, Saleh (IEEE (IEEE Xplore), 2014)
The rocketing grow of demand for communication capacity in fiber back hauls led researchers to a new wireless carrier medium. Laying down optical fibers and maintaining them has proven to be enormously costly and time taking therefore, free space optical (FSO) communication has been introduced to provide fiber like transmission capacity to short reach users. One of the main features of a FSO system is the laser that is used for transmission. In this paper a new multiwavelength erbium doped fiber laser (EDFL) is introduced and its effectiveness in FSO communication is investigated. In our proposed setup 8 channels are extracted from EDFL with each channel transmitting 1.25 Gbps then sent through a single FSO channel. Each channel has a corresponding wavelength which lies on C-band of optical spectrum. Wavelength division multiplexing (WDM) is used to combine 8 signals on transmitter and demultiplexer is used to split signals on receiver. We consider a point to point FSO system with intensity modulation and direct detection (IM/DD). Results of simulation of This single input single output (SISO) FSO system show bit error rate (BER) of (10-9) is achieved at link range of 1.4 km. Reliability of signal is investigated and proved to be efficient by optical signal to noise ratio (OSNR) analysis.